2012
DOI: 10.1163/17087384-12342001
|View full text |Cite
|
Sign up to set email alerts
|

Africa’s Imperial Presidents: Immunity, Impunity and Accountability

Abstract: A fundamental tenet of modern constitutionalism is that nobody, regardless of his status in society, is above the law. Constitutional reforms in the 1990s saw the introduction in many African countries of constitutions which for the first time provide some prospects for promoting constitutionalism and respect for the rule of law. This article reviews the extent to which these reforms have addressed the issue of presidential absolutism and the abuses that go with it. It examines some of the factors that made Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To create a scenario that the initiative is people-centred, the hiring of crowds to populate political gatherings is quickly gaining currency. Led by a singular individual, or group of vocal persons, the movement galvanizes vast crowds, which drum support for the extension of term or removal of terms well-together; the paid crowds paint the picture of the initiative having permission from the grassroots (Fombad & Nwauche, 2012). This ploy, nonetheless, serves to exploit the public.…”
Section: Constitutional Violations By Presidentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To create a scenario that the initiative is people-centred, the hiring of crowds to populate political gatherings is quickly gaining currency. Led by a singular individual, or group of vocal persons, the movement galvanizes vast crowds, which drum support for the extension of term or removal of terms well-together; the paid crowds paint the picture of the initiative having permission from the grassroots (Fombad & Nwauche, 2012). This ploy, nonetheless, serves to exploit the public.…”
Section: Constitutional Violations By Presidentsmentioning
confidence: 99%
“…The other disadvantage of unconstitutional changes is that it occasions economic dislocation and stress to the economy and country in general (Fombad & Nwauche, 2012). To take Zimbabwe as an example, changing the constitutional cap on presidential terms led to severe hyperinflation, which topped at 231 million per cent; the country eventually ceased using its currency and adopted the US dollar as its currency.…”
Section: Refusal To Concede Power To Winning Partiesmentioning
confidence: 99%
“…It is shown that the major reason for the continued retention of the immunity clause in most countries' constitutions is the need to prevent unnecessary distraction of those in executive authority from the primary duty of governance (Obih v. Mbakwe;1984). However, this temporary respite from civil and criminal litigation (domestically and internationally) has proven in many jurisdictions, especially third world countries, to be an ideal cover for the involvement of state officials in unwholesome activities, including corruption, trafficking (drugs and human) and violence (Fombad and Nwauche, 2012;Gberie, 2016). This reality has led to the questioning of whether it is still pertinent to retain this clause in domestic legal systems.…”
Section: The Jurisprudence Of Immunity Clause In Nigeriamentioning
confidence: 99%